2010
DOI: 10.1136/qshc.2009.037531
|View full text |Cite
|
Sign up to set email alerts
|

Patient-held medical records for patients with chronic disease: a systematic review

Abstract: Objectives To determine whether in patients with chronic disease a patient-held medical record (PHR), compared to usual care, improves clinical care, patient outcomes or satisfaction. Design Systematic review. Data sources Databases searched were All EBM (The Cochrane Database of Systematic Reviews, DARE CENTRAL), Medline, CINAHL and EMBASE from 1980 to 16 February 2009. Study selection Two reviewers assessed comparative studies that compared paper-based PHR to usual care for inclusion using a priori study sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 18 publications
(29 reference statements)
3
59
0
1
Order By: Relevance
“…14,18 Some have been used outside of WCC that might be applicable to child preventive care, [66][67][68][69][70][71][72][73][74] and some that are not practice-based could be adapted for use in a practice setting. 75,76 We omitted tools that did not alter the delivery of WCC services (eg, handheld patient records) 77,78 and tools that focused on clinical practice redesign for only 1 WCC topic; these tools should be considered in other reviews. Criteria for defining clinical practice redesign were somewhat stringent and limited the number of articles included.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 Some have been used outside of WCC that might be applicable to child preventive care, [66][67][68][69][70][71][72][73][74] and some that are not practice-based could be adapted for use in a practice setting. 75,76 We omitted tools that did not alter the delivery of WCC services (eg, handheld patient records) 77,78 and tools that focused on clinical practice redesign for only 1 WCC topic; these tools should be considered in other reviews. Criteria for defining clinical practice redesign were somewhat stringent and limited the number of articles included.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73][74][75][76][77][78][79][80][81][82] ( Figure 7). These reviews collectively represented 101 individual RCTs, 29 of which were included in more than one review ( Table 16).…”
Section: Systematic Reviews Identifiedmentioning
confidence: 99%
“…Ko et al 79 reviewed interventions providing patient-held records and Rae-Grant et al 81 explicitly examined self-management programmes.…”
mentioning
confidence: 99%
“…The authors suggested that more high quality studies are needed [106]. Facey et al recommended the use of social science methods to gather evidence on patients’ views [40].…”
Section: Resultsmentioning
confidence: 99%